A Novel Semi‐Analytical (Inertial) Solution for Determining Permeability of Highly Pervious Porous Materials Using the Two‐Reservoir Laboratory Setup - Stanić, Filip; Govedarica, Ognjen; Jaćimović, Nenad; Lekić, Branislava; Ranđelović, Anja (Water resources research, 2023)
Two conventional experimental procedures for determination of the water permeability of saturated porous medium are the constant and the falling head permeability tests. The first one is more applicable on more permeable materials where the outflow from the sample is measured at variety of constant water heads, while the second one is more convenient for low permeable materials, utilizing the continuous measurements of the water head falling due to filtration through the saturated sample. However, neither of the two is useful for materials of high permeability and large cross‐sectional area. The constant head permeability test faces technical issues since a significant and continuous water discharge is required, while the falling head permeability test has limitations due to neglection of the Forchheimer's high‐velocity flow through the sample, but also the influence of inertia on the fluid mass. Here we proposed an approach for determination of the water permeability of saturated porous medium based on the agreement between the measured water level change in two connected reservoirs containing a porous sample and the new semi‐analytical expression describing that change by accounting for the mentioned theoretical deficiencies. This efficient approach has been tested on four pervious paver samples, and results showed satisfactory agreement with the constant head permeability data. It has been also confirmed the proposed semi‐analytical solution is more accurate than the falling head permeability approach in case of highly pervious materials, while for low permeable materials it reduces to the conventional approach. Key Points The constant and the falling head permeability tests are not useful for highly pervious porous samples of large sizes A new semi‐analytical model considering Forchheimer's high‐velocity flow through the sample and inertia of the fluid mass is proposed here This formula is applied on a new permeability test where water flows through a highly pervious sample located between two reservoirs